Revision of the genus Lolliguncula Steenstrup, 1881 (Cephalopoda: Loliginidae) off the Pacific Coast of South America - Cardoso, Franz (2013)
In the present paper the species from the genus LolligunculaSteentrup, 1881 (Cephalopoda: Loliginidae) in Southeastern Pacific Ocean are reviewed. The presence of Lolliguncula (Lolliguncula) panamensisBerry, 1911, Lolliguncula (Loliolopsis) diomedeae Hoyle, 1911 and Lolliguncula (Lolliguncula) argusBrakoniecki and Roper, 1985 are confirmed from Mexican waters to Perú and the species Lolliguncula (Lolliguncula) arguscollected during a cruise of the R/V Anton Bruunfrom 1966 off the coast of South America is recorded for the first time in Peruvian waters. A key to identification of Pacific species is given. We report a diagnostic feature with taxonomic remarks of these species. Updated information on the distribution, biology, and fisheries of each species also is discussed.